Osseoconductive CaTi4-zZrz(PO4)6 Ceramics: Solutions Towards Nonunion, Osteoporosis, and Osteoarthrosis Conditions? - Robert B. Heimann (Ceramics)
Transition (Ti, Zr) metal-substituted calcium hexaorthophosphate CaTi4-zZrz(PO4)6 coatings with an NaSICon structure were deposited by atmospheric plasma spraying (APS) onto Ti6Al4Veli substrates using a statistical design of experiments (SDE) methodology. Several coating properties were determined, including chemical composition, porosity, surface roughness, tensile adhesion strength, shear strength, and solubility in protein-free simulated body fluid (pf-SBF) and TRIS-HCl buffer solution. The biological performance evaluation involved cell proliferation and vitality studies and osseointegration tests of coated Ti6Al4Veli rods intramedullary implanted in sheep femora. After a 6 months observation time, a satisfactory gap-bridging potential was apparent as shown by a continuous, well-adhering layer of newly formed cortical bone. These tests suggest that the coatings possess a suitable osseoconductive potential and present an enhanced expression of bone growth-supporting non-collagenous proteins and cytokines, a high cell proliferation, spreading and vitality, and substantial osseointegration by strong bone apposition. The moderate intrinsic ionic conductivity of CaTi4-zZrz(PO4)6 compounds can be augmented by doping with highly mobile Na+ or Li+ ions to levels that suggest their use in electric bone growth stimulation (EBGS) devices, able to treat nonunion (pseudoarthrosis) and osteoporosis, and that may also support spinal stabilisation by vertebral fusion.